Air void characterisation of HMA gyratory laboratory-moulded samples and field cores using X-ray computed tomography (X-ray CT) - L F Walubita; B Jamison; A E Alvarez; X Hu; C Mushota (Journal of the South African Institution of Civil Engineers, 2012)
The research work presented in this paper deals with the characterisation of the internal structure of hot-mix asphalt (HMA), incorporating both gyratory compacted samples produced in the laboratory and field cores. The primary objective was to determine the optimum trim depth on either end of laboratory-moulded HMA cylindrical samples that would optimise the air void (AV) uniformity in the test specimens. The analysis was based on the X-ray Computed Tomography (X-ray CT) scanning tests and subsequent image analyses. Two Texas HMA mixes, namely a coarse-graded (Type B) and a fine-graded (Type D) mix, with gyratory samples compacted in the laboratory to two different heights (110 and 164 mm) were evaluated for their internal structure in terms of the distribution of both the AV content and AV size. Analysis of the results indicated that the coarse-graded HMA mix (Type B) and the taller (164 mm in height) gyratory-moulded samples would be more likely associated with a more heterogeneous distribution of the AV content and AV size, respectively. Supplemented with field cores, the X-ray CT results indicated significantly poor AV content distribution (i.e. higher AV content and weakest area) at the ends, particularly in the top and bottom 20 mm zone of the samples. Thus, for 150 mm diameter samples of height equal to or greater than 110 mm, trimming a minimum of 20 mm on either side of the gyratory compacted samples should be given due consideration without compromising the specimen aspect ratio and NMAS coverage requirements (NMAS - nominal maximum aggregate size). In general, test specimens should always be cut from the middle zone of the SGC moulded samples where the AV is less heterogeneously distributed.